Decreased malondialdehyde levels in fish (Astyanax altiparanae) exposed to diesel: Evidence of metabolism by aldehyde dehydrogenase in the liver and excretion in water - Garcia, Danielly [UNESP]; Lima, Daína; da Silva, Danilo Grünig Humberto [UNESP]; de Almeida, Eduardo Alves (Elsevier, 2020)
Increased malondialdehyde (MDA) levels are commonly considered an indicator of lipid peroxidation derived from oxidative stress insults promoted by exposure of fish to pollutants. However, a decrease in MDA levels after xenobiotic exposure has been also reported, an effect that is mostly attributed to enhanced antioxidant defenses. In this study, we assessed whether pollutant-mediated MDA decrease would be associated with antioxidant enhancement or with its metabolism by aldehyde dehydrogenase (ALDH) in the liver and gills of lambari (Astyanax altiparanae) exposed to diesel oil (0.001, 0.01, and 0.1 mL/L). MDA levels were decreased in the liver of lambari exposed to diesel. The activities of the antioxidant enzymes, catalase (CAT) and glutathione peroxidase (GPx), were unchanged in the liver, while that of glucose-6-phosphate dehydrogenase (G6PDH) was decreased. In contrast, levels of total glutathione (tGSH) and the activity of glutathione S-transferase (GST) were increased in the liver, which partly support antioxidant protection against lipid peroxidation. More importantly, ALDH activity increased in a concentration-dependent manner, being negatively correlated with MDA levels, indicating MDA metabolism by ALDH. In the gills, diesel exposure increased MDA and lipid hydroperoxide levels, and promoted increases in antioxidant defenses, indicating oxidative stress. Curiously, ALDH activity was undetectable in the gills, supporting the possibility of direct MDA excretion in the water by the gills. Analyses of MDA in the water revealed increased levels of MDA in the aquaria in which the fish were exposed to diesel, compared to control aquaria. A second experiment was carried out in which the fish were intraperitoneally injected with MDA (10 mg/kg) and analyzed after 1, 6, and 12 h. MDA injection caused a time-dependent decrease in hepatic MDA levels, did not alter ALDH, CAT, GPx, and GST activities, and decreased G6PDH activity and tGSH levels. In the gills, MDA injection caused a slight increase in MDA levels after 1 h, but did not alter GPx, G6PDH, and GST activities. MDA injection also enhanced CAT activity and tGSH levels in the gills. MDA concentration in water increased progressively after 1, 6, and 12 h, supporting the hypothesis of direct MDA excretion as an alternative route for MDA elimination in fish. Our results suggest that the decreased MDA levels after exposure of lambari to diesel oil pollutant probably reflects an association between enhanced antioxidant protection, MDA metabolism, and MDA excretion in water.
Keywords: Aldehyde dehydrogenase; Diesel; Fish; Malondialdehyde; Oxidative stress